2016
DOI: 10.1590/2317-1782/20162015218
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da prematuridade na aquisição da linguagem e na maturação auditiva: revisão sistemática

Abstract: RESUMO Objetivo Verificar quais os prejuízos a prematuridade causa à linguagem e à audição. Estratégia de pesquisa Utilizou-se os descritores language/linguagem, hearing/audição, prematurity/prematuridade nas bases de dados LILACS, MEDLINE, Biblioteca Cochrane e Scielo. Critérios de seleção Ensaios randomizados controlados, estudos de intervenção não randomizados e estudos descritivos (transversais, de coorte, projetos de caso-controle). Análise dos dados Os artigos foram avaliados independentemente por do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 43 publications
0
8
1
5
Order By: Relevance
“…We found no difference between preterm newborns/SGA and preterm newborns/AGA (Table 3) regarding language development, similar to another study (12) . The literature reported that SGA preterm infants have a significant delay in total language development (7,8) . However, in this study, language differences occurred more frequently in AGA neonates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found no difference between preterm newborns/SGA and preterm newborns/AGA (Table 3) regarding language development, similar to another study (12) . The literature reported that SGA preterm infants have a significant delay in total language development (7,8) . However, in this study, language differences occurred more frequently in AGA neonates.…”
Section: Discussionmentioning
confidence: 99%
“…The literature shows that preterm infants have worse performance in language tests and skills such as gross motor, fine-adaptive motor and personal-social compared to term children (1)(2)(3) . On the other hand, some studies report that the language impairment not as a condition related to prematurity but related to factors such as gestational age (4)(5)(6)(7) and birth weight (4)(5)(6)(7)(8) . These last two variables are believed to negatively influencing the development of pre-linguistic skills and language outcomes in preterm children (7) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prematurity is one of the most important biological factors of identifying the infant's development, once it has been reported as a risk factor that most exerts child cognitive, language and motor development delay and as the main determinant of morbidity and mortality in newborns (9)(10)(11) . The highest preterm infants survival requires its monitoring, as there are studies that found deficits in preterm infants, when evaluated in visual motor skills, perception (visual, auditive, tactile and kinesthetic), and praxis in comparison to term infants.…”
Section: Introductionmentioning
confidence: 99%
“…Considerando-se especificamente a área da linguagem, por sua vez, verificouse que este domínio, assim como seus subdomínios de linguagem expressiva ou receptiva, foi o que apresentou mais prejuízo nas crianças nascidas prematuras, em relação às outras áreas do desenvolvimento. No estudo de revisão sistemática de Rechia, Oliveira, Crestani, Biaggio e Souza (2016), observou-se que, na maioria dos estudos a condição de prematuridade ao nascer relacionava-se à aquisição de habilidades de linguagem nos primeiros anos de idade das crianças. A prematuridade, assim como os aspectos relacionados a mesma (nível de prematuridade, baixo peso e intercorrências clínicas ao nascer), mostrou impacto negativo na aquisição da linguagem no desenvolvimento das crianças.…”
Section: A Avaliação Do Desenvolvimento De Crianças Por Meio Das Escaunclassified